2023
DOI: 10.3390/s23031225
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Colorectal Polyps from Colonoscopy Using Machine Learning: A Survey on Modern Techniques

Abstract: Given the increased interest in utilizing artificial intelligence as an assistive tool in the medical sector, colorectal polyp detection and classification using deep learning techniques has been an active area of research in recent years. The motivation for researching this topic is that physicians miss polyps from time to time due to fatigue and lack of experience carrying out the procedure. Unidentified polyps can cause further complications and ultimately lead to colorectal cancer (CRC), one of the leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 80 publications
0
0
0
Order By: Relevance
“…The table shows that the AP and IoU values for YOLOv4 and YOLOv3-spp are all above 0.81, indicating that the two YOLO models detect polyps to an adequate level. This finding aligns with what previous research has reported [34]. For instance, Doniyorjon et al [35] tested five YOLO algorithms (i.e., YOLOv3, YOLOv3-tiny, YOLOv4, YOLOv4tiny, and YOLOv4-tiny with the Inception-ResNet-A block), and all models were found to achieve at least 89% training accuracy and 85% testing accuracy.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The table shows that the AP and IoU values for YOLOv4 and YOLOv3-spp are all above 0.81, indicating that the two YOLO models detect polyps to an adequate level. This finding aligns with what previous research has reported [34]. For instance, Doniyorjon et al [35] tested five YOLO algorithms (i.e., YOLOv3, YOLOv3-tiny, YOLOv4, YOLOv4tiny, and YOLOv4-tiny with the Inception-ResNet-A block), and all models were found to achieve at least 89% training accuracy and 85% testing accuracy.…”
Section: Resultssupporting
confidence: 89%
“…To the best of our knowledge, this study may be the first attempt to create a two-stage network by combining U-Net and YOLOv4. As ELKarazle et al ( [34], p. 10) argued, "the YOLO architecture has been the preferred go-to solution for real-time detection tasks as it can process 45 frames per second". This feature makes it popular among researchers and one of the most used methods for polyp detection.…”
mentioning
confidence: 99%
“…R-CNN usa redes neurais convolucionais para localizar objetos de interesse e realizar a extração de características de forma independente de cada região de interesse para processamento posterior. Alguns trabalhos apresentaram bons resultados na detecção de pólipos utilizando modelos baseados no modelo R-CNN, detectando pólipos de formas e tamanhos distintos [ELKarazle et al 2023].…”
Section: Trabalhos Relacionadosunclassified
“…A aprendizagem profunda (deep learning) é um ramo da IA que se baseia em redes neurais profundas e tem a capacidade de extrair automaticamente características relevantes em imagens médicas. Dessa forma, estudos recentes têm surgido sobre o uso de modelos de redes neurais convolucionais para detecção de pólipos em imagens de exames de colonoscopia [ELKarazle, K. et al 2023].…”
Section: Introductionunclassified
See 1 more Smart Citation